2022-RA-222-ESGO Quality of life after extended pelvic exenterations. (20th October 2022) - Lednický, Štefan; Hoschlová, Eva; Sláma, Jiří; Wiesnerová, Markéta; Mitáš, Petr; Matějovský, Zdeněk; Schneiderová, Michaela; Dundr, Pavel; Němejcová, Kristýna; Burgetová, Andrea; Zámečník, Libor; Vočka, Michal; et al.
Abstract : Introduction/Background: Pelvic exenteration (PE) remains a standard of care procedure in patients with recurrent pelvic malignancies, especially after primary radiotherapy. New procedures allow to reach free surgical margins in selected patients with tumours attaching/invading pelvic side-wall structures. However, little has been published about quality of life (QoL) after these more extensive surgeries, carrying new types of morbidity especially after resection of large nerves (femoral and sciatic), vessels, or pelvic bones. The aim of the presented study was to compare the quality of life of patients after PE and extended pelvic exenteration (EPE). Methodology: Data from 74 patients who underwent PE (42) or EPE (32) between 2004 to 2019 at a single tertiary gynae-oncology centre in Prague were analysed. EPEs were defined as procedures including resection of internal, external, or common iliac vessels, pelvic side-wall muscles, large pelvic nerves, or pelvic bones ( figure 1 ). Quality of life assessment was performed in surviving patients using EORTC QLQ-C30, EORTC CX-24, and QOLPEX questionnaire developed and validated specifically for patients after extensive pelvic procedures. Two sided Mann-Whitney U test with Bonferroni correction was used for QoL comparisons. Results: With median follow-up of 23.5 months, median overall survival in the whole cohort was 45 months, and median disease-specific survival 49 months. No significant differences in survival were observed between the groups ( P >0.999). Thirty-one patients participated in the QoL surveys (20 PE, 11 EPE). Most patients reported good level of physical, emotional, and cognitive functions. No evidence of QoL difference between groups was found, nor did we observe differences in the willingness to undergo treatment again. Both groups reported good satisfaction with their respective therapy Conclusion: EPE are associated with similar post-treatment QoL and survival as traditional PE. These procedures offer potentially curative treatment option for patients with recurrent pelvic tumour attaching/invading pelvic wall structures.